Pendampingan Manajemen Kesekretariatan Organisasi Pemuda Desa Melalui Aplikasi E-Archive - Wati, Vera; Widarti, Erni; Erkamim, Moh; Wartono, Wartono; Pamungkas, Muh. Rizal F.; Karsono, Danarti; Setyawati, Nisrina Yulia; Rundi, Allesandro U.B.; Khofid, Adi Nur (Madani : Indonesian Journal of Civil Society, 2025)
Secretarial management in village organizations is an important part of the sustainability of its operations because the management of activities and documentation containing information functions as a set of assets for the organization. Thus, a systematic approach to secretarial management facilitates the process of searching and retrieving documents when needed. However, several village organizations, such as Ikatan Pemuda Pemudi Banjarsari (IPPB), still manage documents manually, which can increase the risk of losing documents due to irregular storage. Referring to this problem, is the basis for the need for community service activities in the IPPB organization to implement a more modern and organized document management system through the Android-based E-Archive application. The activity methodology is based on organizational participation and empowerment, with the main priority being the needs of the community or organization. The implementation of PKM began with participants installing E-Archive on their respective devices, followed by demonstration assistance, and Q&A. The results of this service went smoothly, with this activity attended by representatives of organizational advisors and IPPB core administrators. Assistance focused on installing the application has been successfully carried out on each device, and its management has been carried out successfully according to its features. The facilities provided by multi-user E-Archive allow use according to each role in the IPPB organization. The presence of E-Archive technology solutions with IPPB secretarial management is more efficient because it can be easily accessed via smartphone and provides better storage space compared to manual document storage methods.